2009
DOI: 10.1021/jm901098m
|View full text |Cite
|
Sign up to set email alerts
|

Function-Oriented Biosynthesis of β-Lactone Proteasome Inhibitors in Salinispora tropica

Abstract: The natural proteasome inhibitor salinosporamide A from the marine bacterium Salinispora tropica is a promising drug candidate for the treatment of multiple myeloma and mantle cell lymphoma. Using a comprehensive approach that combined chemical synthesis with metabolic engineering, we generated a series of salinosporamide analogues with altered proteasome binding affinity. One of the engineered compounds is equipotent to salinosporamide A in inhibition of the chymotrypsin-like activity of the proteasome, yet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 32 publications
1
52
1
15
Order By: Relevance
“…As an alternative approach, we focused on proteasome inhibitors, which efficiently block LT killing of murine macrophages, 7,15,36 and which have been used in vivo. [37][38][39][40] Consistent with findings in murine macrophages, we found that the proteasome inhibitor MG132 blocked LT killing of susceptible rat (F344) BMMs (Figure 1, B and C). The water-insoluble MG132, however, is like the general caspase-1 inhibitor Boc-d-cmk, not suitable for in vivo usage.…”
Section: Proteasome Inhibitors Block Lt Killing Of Susceptible Rat Masupporting
confidence: 89%
See 1 more Smart Citation
“…As an alternative approach, we focused on proteasome inhibitors, which efficiently block LT killing of murine macrophages, 7,15,36 and which have been used in vivo. [37][38][39][40] Consistent with findings in murine macrophages, we found that the proteasome inhibitor MG132 blocked LT killing of susceptible rat (F344) BMMs (Figure 1, B and C). The water-insoluble MG132, however, is like the general caspase-1 inhibitor Boc-d-cmk, not suitable for in vivo usage.…”
Section: Proteasome Inhibitors Block Lt Killing Of Susceptible Rat Masupporting
confidence: 89%
“…We therefore focused on the water-soluble proteasome inhibitors bortezomib and salinosporamide-A (NPI-0052), which have been widely used in animals and humans. [37][38][39][40] Bortezomib and NPI-0052 effectively blocked cytolysis in primary F344 BMMs at significantly lower concentrations than MG132 ( Figure 3A). NPI-0052 was particularly potent, protecting macrophages at concentrations 100 times lower than MG132 and approximately 20 times lower than bortezomib (Figure 3A).…”
Section: Proteasome Inhibitors Block Lt Killing Of Susceptible Rat Mamentioning
confidence: 99%
“…Two salinosporamide derivatives with saturated cyclohexane or cyclopentane rings were prepared by mutasynthesis, through administration of derivatives and branched-chain amino acids to a culture of the S. tropica salX mutant strain. [29] To establish the function of cinQ in the salinosporamide gene cluster we inactivated the gene by insertion of an inactivation plasmid (pCN2) into the Streptomyces JS360 genome, leading to complete elimination of cinnabaramide biosynthesis in the mutant. When we attempted to restore product formation by feeding cyclopentyl-dl-alanine to the culture, new compounds exhibiting the expected masses were indeed detected.…”
Section: Resultsmentioning
confidence: 99%
“…In the cell cycle of normal human fibroblasts, -carotene has a delaying effect on the G1 phase [87] which is related to the expression of p21 waf1/cip1 protein (an inhibitor of CDK) [88]; in colon cancer, the presence of -carotene has been associated to a reduced expression of cyclin A (regulator of G2/M progression) [89]; in leukemia cells, the inhibition of cell cycle progression is attributed to the up-regulation of PPAR signaling pathway and the expression of Nrf2, an important transcription factor in Keap 1-Nnf2/EpRE/ARE signaling pathway [90]; therefore, the in vitro effect of -carotene on the cell cycle depends on the studied cell line. On the other hand, -carotene influences and enhances cellular apoptosis by modulating the expression of regulatory genes in cancer cell lines such as colon [89], leukemia [91], melanoma [92], and breast [93].…”
Section: Intervention In Cell Cyclementioning
confidence: 99%
“…The apoptosis mechanism in hepatoma cell cancer has been attributed to depletion of GSH levels [94], and in leukemia cells to down-regulation of Bcl-2 protein [96]. The inhibition of cell cycle progression and apoptosis mechanisms are attributed to the up-regulation of PPAR signaling pathway and the expression of Nrf2, an important transcription factor in Keap 1-Nnf2/EpRE/ARE signaling pathway [90].…”
Section: Intervention In Cell Cyclementioning
confidence: 99%